1996
DOI: 10.1063/1.868976
|View full text |Cite
|
Sign up to set email alerts
|

Hopf bifurcation in wakes behind a rotating and translating circular cylinder

Abstract: A low-dimensional Galerkin method, initiated by Noack and Eckelmann ͓Physica D 56, 151 ͑1992͔͒, for the prediction of the flow field around a stationary two-dimensional circular cylinder in a uniform stream at low Reynolds number is generalized to the case of a rotating and translating cylinder. The Hopf bifurcation describing the transition from steady to time-periodic solution is investigated. A curve indicating the transitional boundary is given in the two-dimensional parameter plane of Reynolds number Re a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
24
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 13 publications
9
24
0
Order By: Relevance
“…While many studies are available at moderate to high Reynolds numbers at which the flow field is three-dimensional (e.g., see [9][10][11][12]), since the present work is concerned with the steady flow regime, the ensuing discussion is limited to the steady flow regime. At Re = 46-47, the flow becomes unsteady even for a [13]. However, subsequent more detailed studies [6,8] also point to the occurrence of two more transitions.…”
Section: Previous Workmentioning
confidence: 84%
“…While many studies are available at moderate to high Reynolds numbers at which the flow field is three-dimensional (e.g., see [9][10][11][12]), since the present work is concerned with the steady flow regime, the ensuing discussion is limited to the steady flow regime. At Re = 46-47, the flow becomes unsteady even for a [13]. However, subsequent more detailed studies [6,8] also point to the occurrence of two more transitions.…”
Section: Previous Workmentioning
confidence: 84%
“…Their results show that, at higher rotational velocity, the Nusselt number is almost independent of Reynolds number and the thermal boundary conditions. The suppression of the von Karman vortex street was also reported numerically by Hu et al (1996) and experimentally by Dol et al (2008) and Lam (2009) for isothermal flow.…”
Section: Introductionmentioning
confidence: 79%
“…For aiding buoyancy at a super-critical Re, the VS suppression was found experimentally [2] for Re ¼ 800 and numerically [3e6] at Ri ¼ 0. 15 for Re ¼ 100. VS suppression under the effect of aiding buoyancy at Ri ¼ 0.12 for Re ¼ 100 and at Ri ¼ 0.2 for Re ¼ 200 was reported by Patnaik et al [5].…”
Section: Introductionmentioning
confidence: 96%
“…For a super-critical Re ¼ 50, suppression of vortex shedding at a critical rotational velocity a > a I was first predicted by Hu et al [15] using a lowdimensional Galerkin method. Later, Kang et al [16] observed no onset of vortex shedding regardless of a at a sub-critical Re ¼ 40.…”
Section: Introductionmentioning
confidence: 97%